Generation of Thyroid Tissues From Embryonic Stem Cells via Blastocyst Complementation In Vivo - Ran, Qingsong; Zhou, Qiliang; Oda, Kanako; Yasue, Akihiro; Abe, Manabu; Ye, Xulu; Li, Yingchun; Sasaoka, Toshikuni; Sakimura, Kenji; Ajioka, Yoichi; Saijo, Yasuo (Frontiers in Endocrinology, 2020)
The generation of mature, functional, thyroid follicular cells from pluripotent stem cells would potentially provide a therapeutic benefit for patients with hypothyroidism, but in vitro differentiation remains difficult. We earlier reported the in vivo generation of lung organs via blastocyst complementation in fibroblast growth factor 10 (Fgf10), compound, heterozygous mutant (Fgf10 Ex1mut/Ex3mut) mice. Fgf10 also plays an essential role in thyroid development and branching morphogenesis but any role thereof in thyroid organogenesis remains unclear. Here, we report that the thyroids of Fgf10 Ex1mut/Ex3mut mice exhibit severe hypoplasia and we generate thyroid tissues from mouse embryonic stem cells (ESCs) in Fgf10 Ex1mut/Ex3mut mice via blastocyst complementation. The tissues were morphologically normal and physiologically functional. The thyroid follicular cells of Fgf10 Ex1mut/Ex3mut chimeric mice were derived largely from GFP-positive mouse ESCs although the recipient cells were mixed. Thyroid generation in vivo via blastocyst complementation will aid functional thyroid regeneration.